Germinal Center Formation, Immunoglobulin Production and Hindlimb Nociceptive Sensitization after Tibia Fracture - Li, Wen-Wu (Brain Behav Immun, 2020)
Emerging evidence suggests that Complex Regional Pain Syndrome (CRPS) is in part a post-traumatic autoimmune disease mediated by an adaptive immune response after limb injuries. We previously observed in a murine tibial fracture model of CRPS that pain-related behaviors were dependent upon adaptive immune mechanisms including the neuropeptide-dependent production of IgM for 5 months after injury. However, the time course of induction of this immune response and the demonstration of germinal center formation in lymphoid organs has not been evaluated. Using the murine fracture model, we employed behavioral tests of nociceptive sensitization and limb dysfunction, serum passive transfer techniques, western blot analysis of IgM accumulation, fluorescence-activated cell sorting (FACS) of lymphoid tissues and immunohistochemistry to follow the temporal activation of the adaptive immune response over the first 3 weeks after fracture. We observed that: 1) IgM protein levels in the skin of the fractured mice were elevated at 3 weeks post fracture, but not at earlier time points, 2) serum from fracture mice at 3 weeks, but not 1 and 2 weeks post fracture, had pro-nociceptive effects when passively transferred to fractured muMT mice lacking B cells, 3) fracture induced popliteal lymphadenopathy occurred ipsilateral to fracture beginning at 1 week and peaking at 3 weeks post fracture, 4) a germinal center reaction was detected by FACS analysis in the popliteal lymph nodes from injured limbs by 3 weeks post fracture but not in other lymphoid tissues, 5) germinal center formation was characterized by the induction of T follicular helper cells (Tfh) and germinal center B cells in the popliteal lymph nodes of the injured but not contralateral limbs, and 6) fracture mice treated with the Tfh signaling inhibitor FK506 had impaired germinal center reactions, reduced IgM levels, reduced nociceptive sensitization, and no pronociceptive serum effects after administration to fractured muMT mice. Collectively these data demonstrate that tibia fracture induces an adaptive autoimmune response characterized by popliteal lymph node germinal center formation and Tfh cell dependent B cell activation, resulting in nociceptive sensitization within 3 weeks.